Dynamic behaviour of bio-based and recycled materials for indoor environmental comfort. (30th June 2019) - Romano, Abbie; Bras, Ana; Grammatikos, Sotirios; Shaw, Andy; Riley, Mike
Highlights: Bio-based materials are examined in terms of MBV, microstructure and latent heat. 11 bio-based insulation materials and thermoplastic recycled polymer were analysed. Only half the samples revealed equivalent efficient moisture transfer. Latent heat tests highlight the good performance of wool and saw mill residue. Abstract: UK construction industry contributes 120 Mt of waste every year. Bio-based building materials may be a solution for this problem, as they combine re-use and recycling abilities together with hygroscopic characteristics, leading to buildings energy savings. For the first time, the dynamic response to hygrothermal changes of bio-based materials is examined in terms of Moisture Buffering Value (MBV), dry/wet thermal conductivity, microstructure, density and latent heat through daily cycles. It is shown that MBV is a useful tool for characterisation but needs to be combined with the shape of the change in mass of the final hygrothermal cycle. Mastering this is required to obtain significant improved indoor environment quality in buildings. Ten samples of bio-based insulation materials and one thermoplastic recycled polymer were analysed (wool, hemp, saw mill residue, wood, straw, cork and polyethylene terephthalate). Saw and wool are the most promising, as materials exhibit dynamic response to hygrothermal changes. Only half the amount of samples revealed equivalent efficient moisture transfer to be able to desorb the adsorbed quantity of water. Latent heat of vaporisation and condensation tests led to the conclusion that samples of wool and saw mill residue can qualify as bio-based materials for 'green' panels.